2015 IEEE 6th International Workshop on Computational Advances in Multi-Sensor Adaptive Processing (CAMSAP) 2015
DOI: 10.1109/camsap.2015.7383817
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying uncertainty in variable selection with arbitrary matrices

Abstract: Probabilistically quantifying uncertainty in parameters, predictions and decisions is a crucial component of broad scientific and engineering applications. This is however difficult if the number of parameters far exceeds the sample size. Although there are currently many methods which have guarantees for problems characterized by large random matrices, there is often a gap between theory and practice when it comes to measures of statistical significance for matrices encountered in real-world applications. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The third specification we consider for our hierarchical prior is the popular Spike-and-Slab prior, and follows very closely the approach described in van den Boom et al (2015a). While it is possible to cast this prior in the hierarchical form of (9) (see for example Gri n and Brown, 2010, p. 175), we follow the literature and write this prior as an explicit mixture of distributions…”
Section: Spike-and-slabmentioning
confidence: 99%
See 3 more Smart Citations
“…The third specification we consider for our hierarchical prior is the popular Spike-and-Slab prior, and follows very closely the approach described in van den Boom et al (2015a). While it is possible to cast this prior in the hierarchical form of (9) (see for example Gri n and Brown, 2010, p. 175), we follow the literature and write this prior as an explicit mixture of distributions…”
Section: Spike-and-slabmentioning
confidence: 99%
“…Also, unlike the approximation methods that rely on the restrictive natural conjugate prior (e.g., Banbura et al, 2010;Giannone et al, 2015), our suggested approach integrates hierarchical shrinkage within an independent prior setting. We capitalize on the e cient algorithm of van den Boom et al (2015a) designed for a univariate regression, and further develop it to address the complexities of high-dimensional VARs. In particular, we first rewrite the VAR in its fully recursive form, which allows equation-by-equation estimation (Carriero et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To upper bound the second term in (27) let (Z, Z E ) be defined according to Z = ΘX and Z E = ΘX E where the relationship between X and X E is given by (26). Conditioned on Θ and the event X ∈ E, we have Z ∼ P 2 and Z E ∼ P 3 , and thus…”
Section: Proofmentioning
confidence: 99%